Utilization of Durian Skin as Raw Materials of Art Paper - Sukma Budi Ariyani; Hidayati Hidayati (Biopropal Industri, 2012)
This research was to utilize solid waste of durian (durian skin) into economically valuable products. The purpose of this research was to obtain a decorative paper or art paper which can be used as a wide range of creative products such as photo frames, tissue boxes, pencil boxes and others. The research was carried out by destroying the skin of durian and other materials to form slurry and then molded and dried. Assessment of art paper quality was based on the beauty of its performance because it was display the fibers on the surface of the paper. It has been carried out analysis of gramatur, tear resistance, moisture content and ash content of the paper produced by durian skin. Paper with gramatur value, moisture content, low ash content and high tear resistance was the good quality paper. For gramatur and water content testing, a paper which was given a red ocher dye (D) is a paper that has the lowest value of gramatur and water content, each of 0.0212 g/cm2 and 7.77%. While the ash content and tear resistance testing, colored paper with mangosteen peel 17% (E) has a low ash content (0.056%) and high tear resistance (104 times fold).